Дарование не имеет пола. Женщины писательницы и поэтессы России первой половины XIX века - Власенко, Людмила Васильевна (My University, 2014)
Ознакомить с работой забытых женских писательниц первой половины XIX столетия. Обосновать основные темы и причины написания их работ, проанализировать сходства и разницу их творческой деятельности в течение данного периода. The work of forgotten women-authoresses of the first half of XIX of century is acquaint, to ground basic themes and reasons of writing of their works, analyse similarities and difference of their creative activity during the given period. Historical and public pre-conditions of development of the woman writing are found out.
Keywords: стих; женские писательницы; работа; verse; work; women-authoresses; кафедра ділової іноземної мови та міжнародної комунікації